What are the main future opportunities in the IoT domain for Computer Science and Information System Prospects? - Zainuddin, Ahmad Anwar (KICT, IIUM, 2022)
Many methods and frameworks are indeed being developed to address cloud-based modelling issues. As a result, now is the time to propose robust and flexible mechanisms for use in the Internet of Things (IoT) industry to overcome domain-specific challenges. This segment examines various readily accessible and easily customizable frameworks which are prevalent in the designed system and some recommended areas in IoT.